The Literacy Test and Its Making - Fairchild, Henry Pratt (Quarterly Journal of Economics, 1917)
Noteworthy provisions, other than the literacy test, in the act of 1917, 448. — The literacy test itself significant of a change in public opinion, 449. — The earlier acts aimed at selection only, 451. — The literacy test a measure of restriction, 452. — The bill of 1897, vetoed by President Cleveland, 453. — Speaker Cannon's successful manoeuvers against a similar bill in 1906, 455. — President Taft's veto of 1913, 456. — President Wilson's veto of 1915, 459. — The act of 1917 finally passed over the veto, 459.